Effects of Amino Acids and Their Mechanisms in Alzheimer’s Disease: Narrative Review - Yuliani, Sapto; Rahmah Annura; Lolita, Lolita; Dwi Utami; Danang Prasetyaning Amukti (Scripta Medica, 2026)
Alzheimer's disease is the most common form of dementia, a complex and progressive neurodegenerative disorder that slowly decreases memory, thinking skills and the ability to perform the simplest tasks. It is characterized by the formation of extracellular amyloid-beta (Aβ) plaques and intracellular neurofibrillary tangles (NFTs). In the human body, amino acids are a source of metabolites and neurotransmitters. Various studies have also proven their association with Alzheimer's disease. Therefore, the research was conducted to review the effects of amino acids and their mechanisms on Alzheimer's disease. This descriptive study is a narrative review of articles on in vivo and in vitro amino acid-induced Alzheimer’s disease in the PubMed and ScienceDirect databases. The selected papers were in English, topic-relevant and published from 2011 to 2021 in journals of Q1, Q2 or Q3 category according to the Scimago Journal & Country Rank. The search yielded 27 relevant articles, but only 22 with 12 types of amino acids were included. Amino acids with positive effects were glutamine, d-serine, selenomethionine, s-adenosylmethionine, d-ribose-l-cysteine, s-allyl-cysteine, N-acetylcysteine, Se-methyl-selenocysteine and l-theanine, whereas some negative results come from homocysteine ​​and N-methylamino-L-alanine. While taurine generally has a positive effect, there is a mechanism that negatively influences Alzheimer's disease. These amino acids are involved in all parts of the pathophysiology mechanism of Alzheimer's disease differently. The mechanisms include preventing (positive impact) or inducing (negative impact) mitochondrial dysfunction, inflammation, oxidative stress, formation of oligomers/plaque Aβ, tau hyperphosphorylation and neuronal/synaptic damage. Thus, not all amino acids have the activity of preventing/treating Alzheimer's disease.
Keywords: Alzheimer’s disease; Amino acids; Mechanism; Review, narrative